2005
DOI: 10.1179/136485905x51283
|View full text |Cite
|
Sign up to set email alerts
|

Where do people from different socio–economic groups receive diagnosis and treatment for presumptive malaria, in south–eastern Nigeria?

Abstract: The relationship between the socio-economic status (SES) of a household and its sources of malaria diagnosis and treatment was explored in south-eastern Nigeria. One aim was to see if, as seems likely, the poorest people generally seek care from 'low-level' providers, such as traditional healers and community-based healthworkers, because of their severe budget constraints. Interviewer-administered questionnaires were used to collect information from 1197 randomly selected respondents from four villages where m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Yet, customers tended to spend more when purchasing drugs to treat fever and cough/cold symptoms. Further, while most fevers were associated with the purchase of anti-malarial drugs, not all were artemisinin-based combination therapies (ACTs) recommended by national treatment guidelines [49]. And since PPMVs are not allowed to perform diagnostics [17, 53], whether febrile and non-febrile illnesses were treated correctly cannot be determined [51, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, customers tended to spend more when purchasing drugs to treat fever and cough/cold symptoms. Further, while most fevers were associated with the purchase of anti-malarial drugs, not all were artemisinin-based combination therapies (ACTs) recommended by national treatment guidelines [49]. And since PPMVs are not allowed to perform diagnostics [17, 53], whether febrile and non-febrile illnesses were treated correctly cannot be determined [51, 54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the government providers, healthcare is provided by various private providers that range from patent medicine dealers (PMDs) to large scale hospitals. The private sector provides over 65% of healthcare delivery in Nigeria [9]. As a general policy, healthcare consumers are expected to pay for curative services, but preventive services are often subsidized.…”
Section: Introductionmentioning
confidence: 99%
“…(Onwujekwe, et al, 2005). There are many public and private healthcare providers of malaria treatment in Nigeria ranging from formal to informal healthcare providers located in urban and rural areas round the country but prompt and appropriate treatment of malaria remains a challenge in the country.…”
Section: Malaria In Nigeriamentioning
confidence: 99%
“…The rural dwellers possibly perceived higher quality of treatment because they may have lower quality expectations and so were satisfied with the treatment they chosen or received. Some authors showed that poor people bear a disproportionate burden of the disease and have poor health-seeking behaviour, thus leading them to seek treatment from "low-level" providers and avoid any form of laboratory-based formal diagnosis, (Goodman, et al, 2001;Onwujekwe, et al, 2005;Worrall, et al, 2005;Filmer, 2005), which consequently increases the burden of the disease on them, (Obinna and Onwujekwe, 2010). This means that the community setting invariably affected the socio-economic status decided to a large extent the perception of quality of treatment (utility function) and hence influenced the most preferred alternative which in turn determined the choices made.…”
Section: Influence Of the Environmentmentioning
confidence: 99%